Éducateurs et éducatrices en « miroir » avec leur public - Charlène Charles (La Nouvelle Revue du Travail)
Care activities have rarely been analysed in light of social workers’ physical efforts. Doing so presents two kinds of challenges. Firstly, the physical skills involved in so-called assistance tasks would have to be identified. Otherwise, the representations conveyed through workers’ appearance – being the kinds of relational tools that child care educators tend to mobilise - also require analysis. Based on an ethnographic survey conducted in child care homes between 2012 and 2016, the article looks at the paradoxical nature of the outreach work being performed today by some of the labour market’s most vulnerable workers. The ultimate aim here is to show how highlighting personal knowledge and experience as well as certain physical attributes – like physical strength and a similarity to customers - helps to validate professionals in situations where they feel trapped by the lack of normal resourcing.